PENGARUH MODEL LEARNING CYCLE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP - Rismaini, Lili (STKIP PGRI Sumatera Barat, 2016)
The result of studying mathematics that is gotlen by students of SMP Pertiwi 1 Padang still low. This case happened because the process of studying still centered on theacher. Beside that, lackness of the ability of mastering also is one of problems that follow the effect of the low of the student’s result. One of the solution that can bedone to solve the problem is by using learning cycle model.The research’s porposes is to know the effect of learning cycle model and the independence of student’s studying in the ability of problem solving student’s mathematics especially on “materi bangun ruang sisi datar”. This research is done in two classes that class as experiment class and control class. In experiment class the studying is done by using learning cycle model. Otherewise, on control class, the studying is done without using convensional model. In each class the student are also divided two group. That is the level of independent high studying and the of independent high stuying and the level of independent low studying the data of the research is gotten from the result of stuying test that concern the independence the student’s studying that is done before and after. Experiment done other wise, the analisys of data is done by using uji t and anava 2 arah.The research of data analisys show that (1) the ability of problem solving the student’s that studying using learning cycle model is higter than the student that studying using convesional model, (2) the ability of problem solving mathematics the group of students the has the independens studying high which using convensional model, (3) the ability of problem solving the students which has the independence the studying low which using learning cycle higter from students that studying use convensional model, (4) there is no interaction between using learning cycle model by the independence studying on effet the ability of problem solving students mathematics.